Diagnóstico da Leishmaniose Visceral utilizando proteínas de Leishmania infantum com função desconhecida - Aliani Moura Fonseca (2013)
Leishmania (Ross, 1903) is a protozoan parasite of major medical and veterinary importance. Visceral Leishmaniasis (VL), also known as kala-azar, is characterized by high fever, substantial weight loss, splenomegaly, hepatomegaly and anemia. Can lead to death if unt reated. The species causing the disease in Brazil are L. infantum (L. chagasi). The VL was primarily zoonosis characterized as rural disease. More recently, it is expanding into medium and large urban areas and has become increasing public health problem in Brazil. The dog is identified as reservoir for L. infantum, due to its susceptibility to infection and high parasitic skin. The epidemiological control of VL in Brazil involves the elimination of seropositive dogs, use of insecticide in houses and peridomestic regions and the systematic treatment of human cases. Serological tests frequently used for screening dogs are: Enzyme Linked Immunosorbent Assay (ELISA) and Immunofluorescence Antibody Test (IFAT). However, these techniques have limitations regarding reproducibility and specificity. During the last years, our group has developed a proteomic study of L. infantum in the search for new diagnostic targets that are more sensitive and specific for detecting both acute and chronic infection. This assay allowed us to identify, among others, hypothetical proteins with potential use in the diagnosis of Canine Visceral leishmaniasis (CVL) that were used for the realization of this project. We selected two hypothetical proteins (C8, C1) were produced recombinantly, using as the vetor plasmid Pet -TeV and expression system as Escherichia coli, BL-21 strain. After purification by affinity chromatography, proteins were used as antigens in serological testing for VL by ELISA. In ELISA with canine serum, C8 antigen had a sensitivity of 75% and specificity of 90%, while the C1 antigen had a sensitivity of 80% and specificity of 60%. On the other hand, in ELISA with human sera, antigens were not efficient to differentiate positive and negative pacients. Furthermore, because we are working with uncharacterized proteins of Leishmania, polyclonal antibodies were produced in rabbits for later use in assays of expression and cellular localization.